The impact of the banking sector on economic structure and growth - Tongurai, Jittima; Vithessonthi, Chaiporn * (Elsevier, 2018)
In this paper, we study the impact of banking sector development on changes in economic structure and growth. We argue that banking sector development has differential effects on industrial sector development and agricultural sector development. We test whether economic structure and growth foster banking sector development. To test our hypotheses, we construct a panel sample of all countries in the world during 1960−2016. We find that banking sector development has a negative effect on agricultural sector development but exerts no effect on industrial sector development. The negative effect of banking sector development on agricultural sector development is only observed for countries with high degrees of banking sector development. Our results further show that agricultural sector development exerts a negative effect on banking sector development while industrial sector development has a positive effect on banking sector development.